Renal Sympathetic Denervation in Patients With Heart Failure With Preserved Ejection Fraction. (17th March 2021) - Kresoja, Karl-Patrik; Rommel, Karl-Philipp; Fengler, Karl; von Roeder, Maximilian; Besler, Christian; Lücke, Christian; Gutberlet, Matthias; Desch, Steffen; Thiele, Holger; Böhm, Michael; Lurz, Philipp
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Arterial hypertension is the most common comorbidity in patients with heart failure with preserved ejection fraction (HFpEF) and mediates adverse hemodynamics through related aortic stiffness and increased pulsatile load. We aimed to investigate the clinical and hemodynamic implications of renal sympathetic denervation (RDN) in patients with HFpEF and uncontrolled arterial hypertension. Methods: Patients undergoing RDN between 2011 and 2018 in a single-center were retrospectively analyzed and classified as HFpEF (n=99) or no HF (n=65). Stroke volume index and aortic distensibility were measured through cardiac magnetic resonance imaging, and left ventricular (LV) systolic and diastolic properties were assessed echocardiographically. Results: At baseline, patients with HFpEF had higher stroke volume index (median 40 [interquartile range, 33–48] versus 33 [26–40] mL/m 2, P =0.002), pulse pressure (69 [63–77] versus 61 [55–67] mm Hg, P <0.001), but lower LV-VPES100mm Hg (18 [10–28] versus 24 [15–40] mL, P =0.007) and aortic distensibility (1.5 [1.1–2.6] versus 2.7 [1.1–3.5] 10 −3 mm Hg −1, P =0.013) as compared to no-HF patients. Systolic blood pressure decreased comparable in patients with HFpEF and no-HF patients following RDN (−9 [−16 to −2], P <0.001). After RDN stroke volume index (−3 [−9 to +3] mL/m 2, P =0.011) decreased and aortic distensibility (0.2 [−0.1 to +1.1] 10 −3 mm Hg −1, P =0.007) and systolic stiffness ( P <0.001) increased in HFpEF patients. LV diastolic stiffness and LV filling pressures as well as NT-proBNP (N-terminal pro-B-type natriuretic peptide) decreased after RDN in patients with HFpEF ( P =0.032, P =0.043, and P <0.001, respectively). Conclusions: Patients with HFpEF undergoing RDN showed increased stroke volume index, vascular, and LV stiffness as compared to no-HF patients. Following RDN those hemodynamic alterations and reduced systolic and diastolic LV stiffness were partly normalized, implying RDN might be a potential therapeutic strategy for arterial hypertension and HFpEF.